Perluasan Pengaturan Diskresi dalam Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja - Utami, Nur Wahyuni (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2022)
AbstractThe enactment of Law Number 11 of 2020 on Job Creation has changed various provisions, one of which is regarding the provisions of discretion which causes an expansion of the regulation on the use of discretion by government officials. This study aims to, first, find out the urgency of expanding the regulation in the enforcement of the Job Creation Act. Second, knowing the legal application of the regulations in the Job Creation Act. The research method applied is normative with the application of laws and conceptual. The results of the study show that, first, the urgency of the abolition of one of the conditions for the use of discretion, namely the condition,